High-performance flexible potassium-doped sodium vanadate positive electrode and preparation method thereof

By introducing potassium-doped modified fibrous sodium vanadate positive electrode material, the problem of irreversible migration of sodium ion battery positive electrode material under high pressure is solved, and the effects of high reversible capacity, excellent rate performance and long cycle life are achieved.

CN119601588APending Publication Date: 2025-03-11XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411670654.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials are irreversible migration problems under high pressure, resulting in low reversible specific capacity, poor rate performance and short cycle life.

Method used

Fibrous potassium doped sodium vanadate (KxNa5-xV12O32-rGO) is used as the positive electrode material. By introducing a small amount of potassium atoms to modify the vanadium oxygen layer structure, the formation of irreversible phase is inhibited, multi-electron reactions and solid solution reactions are activated, and the participation of sodium ions in the redox reaction is increased.

Benefits of technology

It effectively improves the reversible capacity and rate performance of the material, optimizes structural stability, extends the cycle life of the battery, and maintains the stability of the material at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601588A_ABST
    Figure CN119601588A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance flexible potassium-doped sodium vanadate positive electrode and a preparation method thereof, and relates to the technical field of sodium ion batteries, the high-performance flexible potassium-doped sodium vanadate positive electrode is fibrous potassium-doped sodium vanadate, the molecular formula of the potassium-doped sodium vanadate is KxNa5-xV12O32-rGO, and x is greater than or equal to 0.048 and less than or equal to 0.246; according to the high-performance flexible potassium-doped sodium vanadate positive electrode and the preparation method thereof, after a small amount of potassium atoms are introduced for modification, the structure of a vanadium oxide layer in the material is strengthened, generation of an irreversible phase under high pressure is effectively inhibited, stability of the original structure is maintained, and multi-electron reaction and solid solution reaction are effectively activated; more sodium ions are promoted to participate in oxidation-reduction reaction, so that the reversible capacity of the material is improved; the potassium-doped sodium vanadate structure can maintain the stability of the original structure of the material in a completely charged state, and the conversion reaction kinetics is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to sodium ion battery technology, and in particular to a high-performance flexible potassium-doped sodium vanadate positive electrode and a preparation method thereof. Background Art

[0002] Sodium ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive and negative electrodes to work, similar to the working principle of lithium ion batteries. + Insertion and extraction back and forth between the two electrodes. During charging, Na + It is deintercalated from the positive electrode and embedded in the negative electrode through the electrolyte. At the same time, the compensation charge of the electrons is supplied to the negative electrode through the external circuit to ensure the charge balance between the positive and negative electrodes. The opposite is true during discharge. + It is deintercalated from the negative electrode and intercalated into the positive electrode through the electrolyte.

[0003] In view of the irreversible migration of transition metal ions in the high voltage range, the actual reversible specific capacity of transition metal oxide cathode materials is relatively low, less than half of the theoretical specific capacity, and it is difficult to compete with the mainstream ternary and iron lithium cathodes. In order to overcome this limitation, the most effective strategy at present is to dope heterogeneous metal elements into the transition metal layer to inhibit the irreversible migration of transition metals and make the matrix structure in Na + The process of insertion / extraction deviates from the harmful phase transition and enhances the structural stability, while Na + The large radius and molar mass result in slow reaction kinetics of the electrode material and large volume change, which leads to poor rate performance and large loss of irreversible capacity. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance flexible potassium-doped sodium vanadate positive electrode and a preparation method thereof, so as to solve the above-mentioned deficiencies in the prior art.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: a high-performance flexible potassium-doped sodium vanadate positive electrode, which is a fibrous potassium-doped sodium vanadate, wherein the molecular formula of the potassium-doped sodium vanadate is K x Na 5-x V 12 O 32 -rGO, where 0.048≤x≤0.246.

[0006] A method for preparing a high-performance flexible potassium-doped sodium vanadate positive electrode comprises the following steps:

[0007] S1. Put V2O5 powder in a beaker, add oxalic acid solution into the beaker, stir until the color of the solution in the beaker turns blue, then add sodium nitrate solution, potassium nitrate solution and graphene oxide material, continue stirring until the mixture is uniform, and obtain a mixed solution;

[0008] S2, then transferring the mixed solution into a polytetrafluoroethylene reactor, reacting at 200° C., taking out the mixed solution after the reaction is completed, cooling it, washing it with distilled water and alcohol, and filtering it, and drying it in a vacuum drying oven after filtering, and obtaining a film-like potassium-doped precursor sample after drying;

[0009] S3. Place the obtained precursor sample in a tubular atmosphere furnace, heat it to 500° C. at a rate of 2° C. / min in a nitrogen atmosphere, sinter it for 3 hours, and then slowly cool it along with the furnace to finally obtain fibrous potassium-doped sodium vanadate.

[0010] Furthermore, the concentration of the potassium nitrate solution added in S1 is 0.1 g / mL to 0.5 g / mL.

[0011] Furthermore, the reaction time of the reaction at 200° C. in S2 is 12 h.

[0012] Furthermore, the temperature of the vacuum drying oven in S2 is 50°C.

[0013] Compared with the prior art, the high-performance flexible potassium-doped sodium vanadate positive electrode and the preparation method thereof provided by the present invention strengthen the structure of the vanadium oxide layer in the material after modification by introducing a small amount of potassium atoms, effectively inhibit the generation of irreversible phases under high pressure, maintain the stability of its original structure, effectively activate the occurrence of multi-electron reactions and solid solution reactions, promote more sodium ions to participate in redox reactions, thereby improving the reversible capacity of the material;

[0014] While effectively inhibiting the formation of irreversible phases under high pressure, the optimized potassium-doped sodium vanadate structure can maintain the stability of the original structure of the material in the fully charged state, thereby accelerating the conversion reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0016] Figure 1 The X-ray diffraction pattern of potassium-doped sodium vanadate provided in an embodiment of the present invention;

[0017] Figure 2 The charge and discharge curves of the first 100 times of the potassium-doped sodium vanadate positive electrode provided in an embodiment of the present invention;

[0018] Figure 3 A graph showing the rate performance of a potassium-doped sodium vanadate positive electrode provided in an embodiment of the present invention;

[0019] Figure 4 A flow chart of preparing a potassium-doped sodium vanadate positive electrode provided in an embodiment of the present invention;

[0020] Figure 5 A schematic diagram of the process for preparing a potassium-doped sodium vanadate positive electrode provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0022] Embodiment 1:

[0023] See also Figure 1-Figure 5 , a high-performance flexible potassium-doped sodium vanadate positive electrode, which is a fibrous potassium-doped sodium vanadate, and the molecular formula of potassium-doped sodium vanadate is K x Na 5-x V 12 O 32 -rGO(KNVO), where 0.048≤x≤0.246.

[0024] The specific implementation method is that the sodium ions in the fibrous potassium-doped sodium vanadate can be embedded and de-embedded during the charge and discharge process, thereby realizing energy storage and release. After the modification by introducing a small amount of potassium atoms, the structure of the vanadium oxide layer in the material is strengthened, the generation of irreversible phases under high pressure is effectively suppressed, the stability of its original structure is maintained, the multi-electron reaction and the occurrence of solid solution reaction are effectively activated, and more sodium ions are promoted to participate in the redox reaction, thereby improving the reversible capacity of the material; potassium doping can improve the structural stability of sodium vanadate, reduce structural changes during the charge and discharge process, thereby improving the cycle life of the battery; the fibrous structure helps to shorten the transmission path of ions and electrons and improve the charge and discharge rate of the battery.

[0025] Embodiment 2:

[0026] See also Figure 4-Figure 5 This embodiment provides a technical solution based on the first embodiment: a method for preparing a high-performance flexible potassium-doped sodium vanadate positive electrode, comprising the following steps:

[0027] S1. Put V2O5 powder in a beaker, add oxalic acid solution into the beaker, stir until the color of the solution in the beaker turns blue, then add sodium nitrate solution, potassium nitrate solution and graphene oxide material, continue stirring until the mixture is uniform, and obtain a mixed solution;

[0028] S2, then transferring the mixed solution into a polytetrafluoroethylene reactor, reacting at 200° C., taking out the mixed solution after the reaction is completed, cooling it, washing it with distilled water and alcohol, and filtering it, and drying it in a vacuum drying oven after filtering, and obtaining a film-like potassium-doped precursor sample after drying;

[0029] S3. Place the obtained precursor sample in a tubular atmosphere furnace, heat it to 500° C. at a rate of 2° C. / min in a nitrogen atmosphere, sinter it for 3 hours, and then slowly cool it along with the furnace to finally obtain fibrous potassium-doped sodium vanadate.

[0030] The specific implementation method is as follows: take 0.005 mol of V2O5 powder and carefully place it in a clean beaker; prepare 30 mL of 0.5 M oxalic acid solution to ensure that oxalic acid is completely dissolved in deionized water; slowly pour the prepared oxalic acid solution into the beaker containing V2O5 powder, stirring while adding to prevent uneven reaction due to excessive local concentration; continue stirring for 1 hour until the color of the solution in the beaker is observed to turn blue, indicating that V2O5 and oxalic acid have reacted chemically to form a vanadium-containing oxalic acid complex; then, add sodium nitrate solution, 0.3 g / mL potassium nitrate solution, and graphene oxide material that has been processed to an appropriate particle size by a cell crusher in advance to the solution, and continue stirring until all additives are evenly dispersed in the solution to form a uniform mixed solution.

[0031] The above mixed solution was carefully transferred to a polytetrafluoroethylene reactor to ensure good sealing. The reactor was placed in a heating device, the temperature was set to 200°C, and the reaction time was started for 12 hours. During this period, the sealing and temperature stability of the reactor should be checked regularly. After the reaction, the heating source was turned off, and the reactor was allowed to cool naturally to room temperature or the cooling process was accelerated by appropriate means, but the rapid cooling was avoided to cause the product structure to be destroyed. The mixed solution after the reaction was taken out and washed with distilled water several times to remove unreacted oxalic acid, nitrate and other impurities. Then it was washed with anhydrous ethanol to further purify the product and help remove moisture. A suction filtration device was used for solid-liquid separation to collect the solid product. Appropriate pressure can be applied during the suction filtration process to improve the separation efficiency. The solid product after suction filtration was placed in a vacuum drying oven, the temperature was set to 50°C, and dried to constant weight to obtain a precursor sample. During the drying process, the vacuum degree needs to be checked and adjusted regularly to ensure the drying effect.

[0032] Carefully place the dried precursor sample in a tubular atmosphere furnace, ensure that the sample is evenly distributed in the furnace, connect the nitrogen gas source, adjust the gas flow rate to an appropriate value to create a nitrogen protective atmosphere, set the heating program, slowly heat up to 500°C at a rate of 2°C / min, and maintain sintering at this temperature for 3 hours. During this process, pay close attention to the temperature and atmosphere stability in the furnace. After sintering, turn off the heating source and let the sample cool naturally to room temperature with the furnace. To avoid cracks or structural changes caused by rapid cooling, the cooling time can be appropriately extended. Finally, take out the sintered sample to obtain fibrous potassium-doped sodium vanadate K 0.147 Na 4.853 V 12 O 32 -rGO, marking it as KNVO-II.

[0033] Embodiment three:

[0034] This embodiment provides a technical solution based on the second embodiment: replacing step S11 with step S11', placing 0.005 mol V2O5 powder in a beaker, adding 0.5 M (30 mL) oxalic acid solution to the beaker and stirring for 1 hour, and when the color of the solution in the beaker turns blue, adding sodium nitrate solution, 0.1 g / mL potassium nitrate solution and graphene oxide material that has been previously treated by cell crushing, and continuing to stir until the mixture is uniform to obtain a mixed solution;

[0035] In the above step S11', the 0.3 g / mL potassium nitrate solution is replaced by 0.1 g / mL potassium nitrate solution, and the molecular formula of the obtained fibrous potassium-doped sodium vanadate is K 0.048 Na 4.952 V 12 O 32 -rGO, marking it as KNVO-I.

[0036] Embodiment 4:

[0037] This embodiment provides a technical solution based on the embodiment 1: replace step S11 with step S11", place 0.005 mol V2O5 powder in a beaker, add 0.5 M (30 mL) oxalic acid solution to the beaker and stir for 1 hour, when the color of the solution in the beaker turns blue, add sodium nitrate solution, 0.5 g / mL potassium nitrate solution and graphene oxide material that has been previously treated by cell crushing, continue stirring until mixed evenly, and obtain a mixed solution;

[0038] In the above step S11, the 0.3 g / ml potassium nitrate solution is replaced by 0.5 g / mL potassium nitrate solution, and the molecular formula of the obtained fibrous potassium-doped sodium vanadate is K 0.246 Na 4.754 V 12 O32 -rGO, which was labeled KNVO-I II.

[0039] Embodiment five:

[0040] See also Figure 1 This embodiment provides a technical solution based on the first embodiment: performing X-ray diffraction analysis on the prepared flexible potassium-doped sodium vanadate positive electrode material.

[0041] First, prepare Na5V 12 O 32 -rGO (NVO): Weigh 0.005 mol V2O5 powder in a beaker, add 0.5M (30 mL) oxalic acid solution, stir for 1 hour, add sodium nitrate and stir for 0.5 hours after the solution turns blue, then add 9% graphene oxide (2 mg / mL) after cell crushing. Then transfer to a polytetrafluoroethylene reactor, react at 200 ° C for 12 hours, filter after cooling, wash with distilled water and alcohol respectively, dry in a 50 ° C vacuum drying oven, and obtain a film-like precursor sample, which is placed in a tubular atmosphere furnace in a nitrogen atmosphere at a heating rate of 2 ° C / min to 500 ° C for 3 hours, and then cool to obtain a nano-belt Na5V 12 O 32 -rGO composites and labeled them as NVO.

[0042] Then, X-ray diffraction analysis was performed on NVO, KNVO-I, KNVO-II and KNVO-III. It can be seen from the figure that all the diffraction peaks correspond to the standard card (JCPDSP 24-1156). The JCPDSP (or JCPDS) standard card is a standardized tool developed by the International X-ray Diffraction Standardization Organization (JCPDS) for X-ray diffraction data retrieval and analysis.

[0043] This comparison result is crucial, as it not only verifies the accuracy of the experimental data, but also ensures that the structure of the sample under study is consistent with that of the standard substance. No additional diffraction peaks corresponding to impurities appear in the spectrum, indicating that no foreign substances that may affect its purity were introduced during the preparation and processing of the sample, thus ensuring the purity and reliability of the experimental results.

[0044] Further analysis showed that the space group of potassium-doped sodium vanadate was determined to be P21 / m. The space group P21 / m belongs to the monoclinic crystal system, which describes the arrangement of atoms or molecules in the crystal, including its symmetry and periodicity. The confirmation of this space group means that the sample studied has retained its original monoclinic crystal structure.

[0045] It is particularly worth mentioning that the spectrum analysis also revealed the successful preparation of K-doped samples, and the successful doping of K element did not destroy the original crystal structure.

[0046] Embodiment six:

[0047] See also Figure 2-Figure 3 This embodiment provides a technical solution based on the first embodiment: the charge-discharge performance and rate performance of the prepared high-performance flexible potassium-doped sodium vanadate positive electrode are tested.

[0048] The specific implementation method is to use the prepared high-performance flexible potassium-doped sodium vanadate material as the positive electrode, and assemble it with the sodium negative electrode and GF / A glass fiber membrane into a button battery.

[0049] The electrolyte includes solute, solvent and additive. The solute is NaClO4, i.e. sodium perchlorate, which is the electrolyte in the electrolyte, and its concentration is 1mol / L, which means that there is 1 mole of NaClO4 in each liter of electrolyte; the solvent is composed of ethylene carbonate (EC) and dimethyl carbonate (DMC), which is the main part of the electrolyte. EC and DMC are mixed in a mass ratio of 1:1, which means that in the electrolyte, the mass of EC and DMC is equal; the additive is fluoroethylene carbonate (FEC). As an additive of the electrolyte, the amount of FEC added is 5% of the total mass of the electrolyte. FEC can play a variety of roles in the electrolyte, such as improving the cycle performance of the battery and improving the stability of the battery.

[0050] The charge and discharge performance of the button battery was tested using constant current charge and discharge technology. From the charge and discharge curve, it can be observed that the reversible specific capacity of the KNVO-II sample can be as high as 250.1 mAh / g.

[0051] The rate performance of the above button battery was tested using constant current charge and discharge technology, with a test temperature of 25°C, a charge termination voltage of 4.3V, and a discharge termination voltage of 1.5V. When charged and discharged at 0.2C, 0.5C, 1C (260mA / g), 3C, 5C, and 10C, the discharge capacities were 236, 228.8, 214, 189.3, 172.1, and 128mAh / g, respectively. Compared with the unmodified material, the rate performance can be greatly improved.

[0052] After 1000 cycles in the voltage range of 1.5-4.3V, the discharge specific capacity of KNVO-II is as high as over 200mAh / g, and even at a current density of 1300mA / g, the capacity retention rate can still be maintained at over 95%. The reversible specific capacity and rate performance of the material are improved in the high voltage range of 1.5-4.3V, achieving a reversible capacity of 128mAh / g at 10C. While effectively suppressing the generation of irreversible phases under high voltage, the optimized KNVO-II structure can maintain the stability of the original structure of the material in the fully charged state, accelerating the conversion reaction kinetics.

[0053] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A high-performance flexible potassium-doped sodium vanadate positive electrode, characterized in that: It is a fibrous potassium-doped sodium vanadate, the molecular formula of which is K x Na 5-x V 12 O 32 -rGO, where 0.048≤x≤0.

246.

2. A method for preparing a high-performance flexible potassium-doped sodium vanadate positive electrode, characterized in that: The steps include: S1. Put V2O5 powder in a beaker, add oxalic acid solution into the beaker, stir until the color of the solution in the beaker turns blue, then add sodium nitrate solution, potassium nitrate solution and graphene oxide material, continue stirring until the mixture is uniform, and obtain a mixed solution; S2, then transferring the mixed solution into a polytetrafluoroethylene reactor, reacting at 200° C., taking out the mixed solution after the reaction is completed, cooling it, washing it with distilled water and alcohol, and filtering it, and drying it in a vacuum drying oven after filtering, and obtaining a film-like potassium-doped precursor sample after drying; S3. Place the obtained precursor sample in a tubular atmosphere furnace, heat it to 500° C. at a rate of 2° C. / min in a nitrogen atmosphere, sinter it for 3 hours, and then slowly cool it along with the furnace to finally obtain fibrous potassium-doped sodium vanadate.

3. The method for preparing a high-performance flexible potassium-doped sodium vanadate positive electrode according to claim 2, characterized in that: The concentration of the potassium nitrate solution added in S1 is 0.1 g / ml to 0.5 g / ml.

4. The method for preparing a high-performance flexible potassium-doped sodium vanadate positive electrode according to claim 2, characterized in that: The reaction time of S2 at 200° C. is 12 h.

5. The method for preparing a high-performance flexible potassium-doped sodium vanadate positive electrode according to claim 2, characterized in that: The temperature of the vacuum drying oven in S2 is 50°C.